2023
DOI: 10.1002/cjoc.202200780
|View full text |Cite
|
Sign up to set email alerts
|

Reading Time and DNA Sequence Preference of TET3 CXXC Domain Revealed by Single‐Molecule Profiling

Abstract: Comprehensive SummaryRecognition of CpG dinucleotide DNA in epigenetic information flow plays a pivotal role for cellular differentiation and development. The TET3 CXXC domain binds to CpG DNA, serving a basic epigenetic information reading mechanism. During the selective recognition of a CpG motif by a CXXC domain from crowded binding sites in a gene sequence, the protein‐DNA interactions are beyond CpG dinucleotide. However, the selective binding dynamics of CpG within a long DNA context by epigenetic enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…They offer insights into complex molecular events such as drug targeting, molecular interactions, and conformational changes, enabling the dynamic analysis of molecular mechanisms at the single-molecule level. [9] Typically, single-molecule manipulation strategies involve the placement of affinity tags at both ends of the biological macromolecule, for example, at the 3' and 5' ends of nucleic acids or the N and C termini of proteins.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…They offer insights into complex molecular events such as drug targeting, molecular interactions, and conformational changes, enabling the dynamic analysis of molecular mechanisms at the single-molecule level. [9] Typically, single-molecule manipulation strategies involve the placement of affinity tags at both ends of the biological macromolecule, for example, at the 3' and 5' ends of nucleic acids or the N and C termini of proteins.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Previous studies have demonstrated that TET enzymes can oxidize 5mC consecutively to form 5hmC, 5fC, and 5caC. [ 31‐34 ] TDG plays a crucial role in DNA demethylation by recognizing and cleaving the N ‐glycosidic bonds of 5fC and 5caC, leading to basic sites (AP sites). [ 35‐36 ] These AP sites are then cleaved by apurinic/apyrimidinic endonuclease 1 (APE1), which generates a 3'‐OH group and 5'‐phosphate ester (5'‐dRP) termini.…”
Section: Tet‐tdg‐ber Pathwaymentioning
confidence: 99%